Cloning, expression, and sequence analysis of the Bacillus methanolicus C1 methanol dehydrogenase gene. - de Vries, G E (1992)
The gene (mdh) coding for methanol dehydrogenase (MDH) of thermotolerant, methylotroph Bacillus methanolicus C1 has been cloned and sequenced. The deduced amino acid sequence of the mdh gene exhibited similarity to those of five other alcohol dehydrogenase (type III) enzymes, which are distinct from the long-chain zinc-containing (type I) or short-chain zinc-lacking (type II) enzymes. Highly efficient expression of the mdh gene in Escherichia coli was probably driven from its own promoter sequence. After purification of MDH from E. coli, the kinetic and biochemical properties of the enzyme were investigated. The physiological effect of MDH synthesis in E. coli and the role of conserved sequence patterns in type III alcohol dehydrogenases have been analyzed and are discussed.